Parasitism of Copturus aguacatae (Coleoptera: Curculionidae) larvae by Heterorhabditis indica (Rhabditida: Heterorhabditidae) in the laboratory - SÁNCHEZ-SAAVEDRA, MA. GUADALUPE; CORTEZ-MADRIGAL, HIPÓLITO; OCHOA-ESTRADA, SALVADOR (Revista Colombiana de Entomología, 2012)
To evaluate the potential of the nematode Heterorhabditis indica as a biocontrol agent of the avocado stem weevil, Copturus aguacatae, bioassays were planned with larvae of the pest inside and outside of stems in Jiquilpan, Michoacan (Mexico). Outside of stems, second and third instars larvae were exposed to four nematode concentrations:1% (2500 nematodes mL-1), 0.1% (250 nematodes mL-1), 0.01% (25 nematodes mL-1) and 0.001% (2.5 nematodes mL-1). The optimal concentrations and the time required to kill 50% of the population (LT50) were estimated. The bioassays inside of stems included four strategies of application: “baba” (soap) of nopal, gelatin, water, and water + plastic cover. Sponge strips were soaked in a suspension of 500 nematodes mL-1 plus the corresponding treatment. Avocado stems with larvae of the pest collected in Atapan, Michoacán (Mexico) were covered with the sponges and incubated for 15 days; the study conditions were 25 ± 1 °C. The results showed high virulence of H. indica to larvae of the pest. The estimated LT50 was 28.8 h, whereas the interval required to cause 100% mortality was estimated as 44 h. The optimal concentration was 0.1% (250 nematodes mL-1) with a mortality of 93.3% ± 5.7%. However, strong limitations were detected for H. indica to penetrate and infect C. aguacatae inside of the galleries. Although there was a trend for higher mortality in treatments with respect to the control, juvenile nematodes were only recovered from the treatment water + plastic cover.